2003
DOI: 10.1248/bpb.26.501
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Administration of Bromocriptine.

Abstract: Bromocriptine (BRC) is a semi-synthetic ergot alkaloid and it has been used for the treatment of diseases caused by hyperprolactinemia and for some neurological disorders as a dopamine agonist in clinics.1) BRC is mainly used for the inhibition of lactation, 2) treatment of menstrual disorders, 3) Parkinson disease, 4) breast tumours, 5) infertility 6) and brain tumours. 7)Bromocriptine is well absorbed through the GI tract but it has low bioavailability because of the hepatic first pass effect, but many patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 30 publications
(27 reference statements)
0
13
0
Order By: Relevance
“…[19] Chitosan gel mediated delivery of BCT revealed the effectiveness of transdermal route as an alternate to oral delivery. [20] Literature suggests the application of transdermal delivery system to improve the therapeutic efficacy of BCT by avoiding hepatic metabolism and manitaining optimal plasma concentrations for a long period. [20] The present work was designed to investigate the feasibility of using proniosomal gel as transdermal vehicle for BCT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] Chitosan gel mediated delivery of BCT revealed the effectiveness of transdermal route as an alternate to oral delivery. [20] Literature suggests the application of transdermal delivery system to improve the therapeutic efficacy of BCT by avoiding hepatic metabolism and manitaining optimal plasma concentrations for a long period. [20] The present work was designed to investigate the feasibility of using proniosomal gel as transdermal vehicle for BCT.…”
Section: Introductionmentioning
confidence: 99%
“…[20] Literature suggests the application of transdermal delivery system to improve the therapeutic efficacy of BCT by avoiding hepatic metabolism and manitaining optimal plasma concentrations for a long period. [20] The present work was designed to investigate the feasibility of using proniosomal gel as transdermal vehicle for BCT. The influence of the various surfactants and cosurfactants was evaluated on the characteristics of proniosomes.…”
Section: Introductionmentioning
confidence: 99%
“…BRC is available in tablet and capsule dosage form (2.5 --20 mg/day, in divided doses), and these dosage forms exhibit low bioavailability (6%) due to extensive first-pass metabolism and non-targeted delivery results in side effects such as GI side effects, headache and dizziness [16]. The long-acting injectable form, transdermal and vaginal delivery route of BRC have been already reported [17].…”
Section: Introductionmentioning
confidence: 99%
“…Reports on currently available dosage forms, that is, tablet (SicriptinÔ), indicated that it could not cross BBB and, after oral administration of BRC, it exhibits low or incomplete absorption and low bioavailability due to high metabolism in the liver (Vautier et al, 2006). A number of strategies such as drug delivery and drug targeting systems have been investigated for BRC to prevent drug degradation and loss so as to increase its bioavailability with high concentrations of BRC accumulated in the targeted area (Degim et al, 2003). Esposito and coworkers investigated nanolipidic carriers (NLC) of BRC for brain delivery.…”
Section: Introductionmentioning
confidence: 99%